2013
DOI: 10.1080/1062726x.2013.795867
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Effectiveness of Base Crisis Response Strategies in Comparison of Reputation Management Crisis Responses

Abstract: This experimental study found that employing reputation management crisis-response strategies was no better than adopting only the base crisis-response strategy (i.e., instructing and adjusting information) in terms of generating positive responses from the public. Two-sided messages (i.e., sharing both positive and negative information) in crisis communication were found to be more effective than one-sided messages in a victim crisis. In addition, even in a preventable crisis, one-sided messages (i.e., sharin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 29 publications
4
60
0
Order By: Relevance
“…In addition, organizational reputation is better protected by matching response strategies, as compared to mismatching response strategies, no responses, and only information aiming at protecting publics physically and psychologically. Although some individual studies concluded that matching response strategies with crisis clusters do not better protect organizational reputation (e.g., Claeys et al, 2010;Grappi & Romani, 2015;Kim & Sung, 2014), on average, responding to crises strategically based on crisis clusters better protects organizational reputation.…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 96%
See 4 more Smart Citations
“…In addition, organizational reputation is better protected by matching response strategies, as compared to mismatching response strategies, no responses, and only information aiming at protecting publics physically and psychologically. Although some individual studies concluded that matching response strategies with crisis clusters do not better protect organizational reputation (e.g., Claeys et al, 2010;Grappi & Romani, 2015;Kim & Sung, 2014), on average, responding to crises strategically based on crisis clusters better protects organizational reputation.…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 96%
“…The mixed findings on the efficacy of response strategies have not provided sufficient empirical support for this SCCT proposition, because some found that the SCCT-recommended strategies were effective (e.g., Coombs & Holladay, 1996;Sheldon & Sallot, 2008), but others found that matching response strategies with crisis clusters provided no better protection than mismatching response strategies or information disseminated to protect publics physically or psychologically (e.g., Grappi & Romani, 2015;Kim & Sung, 2014). Verhoeven, Van Hoof, Ter Keurs, and Van Vuuren (2012) also found that corporate reputation suffered to the same degree whether the corporation apologized or didn't, both for accidental and preventable crises.…”
Section: Match-reputation Relationshipmentioning
confidence: 92%
See 3 more Smart Citations